S48 The Effect of Angiotensin-Converting Enzyme Inhibition on Skeletal Muscle Dysfunction in Chronic Obstructive Pulmonary Disease: A Randomised Controlled Trial. (19th November 2012) - Shrikrishna, D; Tanner, RJ; Lee, JY; Natanek, SA; Lewis, A; Murphy, PB; Hart, N; Moxham, J; Montgomery, H; Kemp, PR; Polkey, MI; Hopkinson, NS
Abstract : Introduction: Skeletal muscle impairment is a well recognised complication of COPD, predicting mortality in severe disease. 1 Evidence from animal models, genetic studies and observational cohorts suggest a role for the renin-angiotensin system in control of muscle phenotype. 2 We hypothesised that angiotensin-converting enzyme (ACE) inhibition would have a beneficial effect on quadriceps function in patients with COPD. Methods: A single-centre, double-blind randomised controlled parallel-group trial investigating the effect of fosinopril versus placebo on quadriceps muscle dysfunction in COPD patients with quadriceps weakness. Muscle weakness was defined as a quadriceps maximum voluntary contraction (QMVC) less than 120% of the body mass index.1 Measurements: The primary outcome was change in non-volitional quadriceps endurance at 3 months, measured using repetitive magnetic stimulation. QMVC, mid-thigh CT cross-sectional area (MTCSA ), incremental shuttle walk distance (ISWD) and serum inflammatory markers were secondary outcomes. Results: 80 patients were enrolled (mean(SD), 65(8) years, FEV1 43(21)% predicted, 53% male). 67 patients (31 fosinopril and 36 placebo) completed the trial, with the treatment group demonstrating a significant reduction in systolic blood pressure (Δ-10.5mmHg, 95%CI –19.9 to –1.1, p=0.03) and serum ACE activity (Δ-20.4units/L, 95%CI –31.0 to –9.8, p<0.001) compared to placebo. At 3 months, no significant difference was observed in quadriceps muscle endurance half-time (fosinopril Δ5.1s, 95%CI –4.3 to 14.5, p=0.27 vs. placebo Δ4.6s, 95%CI –5.8 to 15.1, p=0.37; between group Δ0.5s, 95%CI –13.3 to 14.3, p=0.94). QMVC improved significantly in both groups (fosinopril Δ1.1kg, 95%CI 0.03 to 2.2, p=0.045 vs. placebo Δ3.6kg, 95%CI 2.1 to 5.0, p<0.0001) with a greater increase in the placebo arm (between group Δ2.5kg, 95%CI 0.7 to 4.3, p<0.01). There was no significant change in MTCSA (p=0.09), ISWD (p=0.51) or serum inflammatory markers (C-reactive protein, p=0.17) between the groups. Stratification based on ACE genotype did not influence study outcomes. Conclusion: This randomised controlled trial found that ACE-inhibition did not improve quadriceps function in a COPD population with quadriceps weakness. Study funded by the Medical Research Council. Trial registration: NCT01014338 . Swallow EB, et al . Thorax 2007; 62:115–20. Shrikrishna D, et al . Clin Sci 2012; 123:487–98.